Charles Ludlam Lives! Charles Bush, Bradford Louryk, Taylor Mac, and the Queer Legacy of the Ridiculous Theatrical Company - Edgecomb, Sean (University of Michigan Press, 2017)
Playwright, actor and director Charles Ludlam (1943-1987) helped to galvanize the Ridiculous style of theater in New York City starting in the 1960s. Decades after his death, his place in the chronicle of American theater has remained constant, but his influence has changed. Although his Ridiculous Theatrical Company shut its doors, the Ludlamesque Ridiculous has continued to thrive and remain a groundbreaking genre, maintaining its relevance and potency by metamorphosing along with changes in the LGBTQ community.